On the Spatial Potential of Russia (The Spatial in the Strategy of Socio-Economic Development of Russia” / Ed. by L.V. Nikiforov. M.: Institute of economics RAN. 2011. 285 p) - N. A. Shmeleva (Vestnik MGIMO-Universiteta)
.